"Simple, clear, and easily understood by the farmer…": On expert–layman communication in American soil science, 1920s–50s. (September 2019) - Arend, Jan
This article presents a case study of how American soil scientists encountered the increasing demands to prove the social utility of their scientific work in the first half of the twentieth century and how this influenced the professional rivalry and competition among them. Previous historical studies of agricultural science in the period have not overlooked the increasing demands for applicability that agricultural scientists were faced with at the time. However, in describing the response of agricultural scientists to these demands, research has focused on the content of their scientific work, that is, their methods, empirical interests, and theories. This study, by contrast, explores how the debates on applied vs. fundamental/basic research in American agricultural science were closely linked to the question of how scientific knowledge could be made understood to laymen and practitioners.